2022
DOI: 10.3390/antiox11122473
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Retention Rates of Synthetic and Natural Astaxanthin in Feeds and Their Effects on Pigmentation, Growth, and Health in Rainbow Trout (Oncorhynchus mykiss)

Abstract: The coloring efficiency and physiological function of astaxanthin in fish vary with its regions. The aim of this study was to compare the retention rates of dietary astaxanthin from different sources and its effects on growth, pigmentation, and physiological function in Oncorhynchus mykiss. Fish were fed astaxanthin-supplemented diets (LP: 0.1% Lucantin® Pink CWD; CP: 0.1% Carophyll® Pink; EP: 0.1% Essention® Pink; PR: 1% Phaffia rhodozyma; HP: 1% Haematococcus pluvialis), or a diet without astaxanthin supplem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 59 publications
0
7
0
1
Order By: Relevance
“…However, in this study, the addition of 100 mg/kg astaxanthin from WUHPA and CSA did not have a significant impact on these flavor-presenting amino acids. Similarly, there was no significant effect on these amino acids when 1% H. pluvialis was included in the diets for rainbow trout [37].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…However, in this study, the addition of 100 mg/kg astaxanthin from WUHPA and CSA did not have a significant impact on these flavor-presenting amino acids. Similarly, there was no significant effect on these amino acids when 1% H. pluvialis was included in the diets for rainbow trout [37].…”
Section: Discussionmentioning
confidence: 93%
“…In this study, dietary inclusion of 100 mg/kg astaxanthin significantly decreased the threonine content in rainbow trout fillet. Conversely, a previous study indicated that the threonine content in the dorsal fillet of rainbow trout increased with the dietary addition of 1% H. pluvialis [37]. The amino acids responsible for flavor and taste typically include glutamic acid, aspartic acid, phenylalanine, alanine, and glycine [36,38].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Dietary astaxanthin may regulate the amino acid metabolism of the hepatopancreas in Exopalaemon carinicauda [33]. In fish, Carophyll ® pink increased the level of umami amino acids (Asp and Glu) [34]. However, further research is required to determine whether carotenoids are the direct reasons for amino acid changes.…”
Section: Discussionmentioning
confidence: 99%
“…Một số nghiên cứu trước đây cũng từng đề cập đến vấn đề này. Cụ thể, việc bổ sung carotenoids giúp tăng màu đỏ và vàng nhưng lại gây tác dụng phụ làm tối màu da ở các loài cá vẹt đỏ Vieja melanurus ♀ × Amphilophus citrinellus ♂, cá dĩa Symphysodon spp., cá tráp đỏ Pagrus pagrus và cá hồi vân Oncorhynchus mykiss [18,23,29,38]. Như vậy, có thể thấy rằng vẫn còn nhiều vấn đề cần làm rõ liên quan đến tác động của astaxanthin bổ sung lên cá khoang cổ nemo, tập trung vào các cơ chế chuyển hóa, hấp thu, đặc biệt là con đường chuyển hóa từ astaxanthin bổ sung thành các sản phẩm trung gian như zeaxanthin và canthaxanthin tích lũy trong cơ thể loài cá này.…”
Section: Thảo Luậnunclassified